Judah in the Reign of Manasseh as Evidenced in Texts during the Neo-Assyrian Period and in the Archaeology of the Iron Age - Bulbach, Stanley Walter
Diss.; Adviser: Вaruch Levine. Order No. 8115534; DissAbstr 42 (1981) 809-A.